Shareholder activism of public pension funds: The political facet - Wang, Yong; Mao, Connie X. (Journal of Banking & Finance, 2015)
This paper studies the political incentive of public pension funds in shareholder activism. Using a sample of shareholder proposals from 1993 to 2013 and a hand-collected data set of the political variables of public pension funds, we document evidence consistent with the “political attention hypothesis.” We find that the number of politicians on public pension fund boards is significantly positively related to the frequency with which portfolio firms are targeted. Moreover, the frequency of social-responsibility proposals by public pension funds increases significantly, as the funds have a greater number of board members running for election to public office. However the frequency of corporate governance proposals is not related to the number of board members running for elections to public office. Furthermore, we document that political connection between a portfolio firm and a public pension fund mitigates the firm’s likelihood of being targeted by the fund with social-responsibility proposals. This result supports the “political contribution hypothesis.” The paper provides direct evidence that public pension-fund board members employ shareholder proposals to enhance their political capital.